Tri-diagonal Matrix Determinant Derivation
📂Matrix Algebra Tri-diagonal Matrix Determinant Derivation X n : = [ x 1 0 ⋯ 0 0 1 x 1 ⋯ 0 0 0 1 x ⋯ 0 0 ⋮ ⋮ ⋮ ⋱ ⋮ ⋮ 0 0 0 ⋯ x 1 0 0 0 ⋯ 1 x ]
X_{n} := \begin{bmatrix}
x & 1 & 0 & \cdots & 0 & 0
\\ 1 & x & 1 & \cdots & 0 & 0
\\ 0 & 1 & x & \cdots & 0 & 0
\\ \vdots & \vdots & \vdots & \ddots & \vdots & \vdots
\\ 0 & 0 & 0 & \cdots & x & 1
\\ 0 & 0 & 0 & \cdots & 1 & x
\end{bmatrix}
X n := x 1 0 ⋮ 0 0 1 x 1 ⋮ 0 0 0 1 x ⋮ 0 0 ⋯ ⋯ ⋯ ⋱ ⋯ ⋯ 0 0 0 ⋮ x 1 0 0 0 ⋮ 1 x The determinant of the tridiagonal matrix X n X_{n} X n defined as above is given by the following.det X n = ∣ X n ∣ = U n ( x 2 )
\det X_{n} = \left| X_{n} \right| = U_{n} \left( {{x} \over {2}} \right)
det X n = ∣ X n ∣ = U n ( 2 x )
U n U_{n} U n represents the Chebyshev polynomials of the second kind of degree n n n .
Proof It should be noted that X n X_{n} X n is not just any tridiagonal matrix but a specific form known as the tridiagonal Toeplitz matrix. This form is particularly useful in the numerical solution of partial differential equations , and the eigenvalues are often of primary interest.
Part 1. ∣ X n + 1 ∣ = x ∣ X n ∣ − ∣ X n − 1 ∣ | X_{n+1} | = x | X_{n} | - | X_{n-1} | ∣ X n + 1 ∣ = x ∣ X n ∣ − ∣ X n − 1 ∣
Laplace expansion : With respect to the chosen i i i rowdet A = ∑ i = 1 n a i j C i j
\det A = \sum_{i=1}^{n} a_{ij} C_{ij}
det A = i = 1 ∑ n a ij C ij
Matrix n × n n \times n n × n $Y_{n} : = \begin{bmatrix} 1 & 1 & 0 & \cdots & 0 & 0
\\ 0 & x & 1 & \cdots & 0 & 0
\\ 0 & 1 & x & \cdots & 0 & 0
\\ \vdots & \vdots & \vdots & \ddots & \vdots & \vdots
\\ 0 & 0 & 0 & \cdots & x & 1
\\ 0 & 0 & 0 & \cdots & 1 & x
\end{bmatrix}을정의하자 . 을 정의하자. 을정의하자 . Y_{n}의첫번째열은 의 첫번째 열은 의첫번째열은 (1, 0 , \cdots , 0)으로써 , 첫번째성분을제외하면영벡터가되므로첫번째열을포함한여인자는 으로써, 첫번째 성분을 제외하면 영벡터가 되므로 첫번째 열을 포함한 여인자는 으로써 , 첫번째성분을제외하면영벡터가되므로첫번째열을포함한여인자는 0$ holds. Therefore,
∣ Y n ∣ = 1 ⋅ ∣ X n − 1 ∣ − 1 ⋅ 0 + 0 ⋅ 0 − ⋯ ± 0 ⋅ 0 = ∣ X n − 1 ∣
| Y_{n} | = 1 \cdot | X_{n-1} | - 1 \cdot 0 + 0 \cdot 0 - \cdots \pm 0 \cdot 0 = | X_{n-1} |
∣ Y n ∣ = 1 ⋅ ∣ X n − 1 ∣ − 1 ⋅ 0 + 0 ⋅ 0 − ⋯ ± 0 ⋅ 0 = ∣ X n − 1 ∣
Similarly, by Laplace expansion ,
∣ X n + 1 ∣ = x ⋅ ∣ X n ∣ − 1 ⋅ ∣ Y n ∣ + 0 ⋅ 0 − ⋯ ± 0 ⋯ 0 = x ∣ X n ∣ − ∣ X n − 1 ∣
| X_{n+1} | = x \cdot | X_{n} | - 1 \cdot | Y_{n} | + 0 \cdot 0 - \cdots \pm 0 \cdots 0 = x | X_{n} | - | X_{n-1} |
∣ X n + 1 ∣ = x ⋅ ∣ X n ∣ − 1 ⋅ ∣ Y n ∣ + 0 ⋅ 0 − ⋯ ± 0 ⋯ 0 = x ∣ X n ∣ − ∣ X n − 1 ∣
Part 2. ∣ x n ∣ = U n ( x 2 ) \displaystyle | x_{n}| = U_{n} \left( {{x} \over {2}} \right) ∣ x n ∣ = U n ( 2 x )
Let’s define proposition P ( n ) : ∣ x n ∣ = U n ( x 2 ) \displaystyle P(n) : | x_{n}| = U_{n} \left( {{x} \over {2}} \right) P ( n ) : ∣ x n ∣ = U n ( 2 x ) and apply mathematical induction .
For n = 1 n=1 n = 1 ,
∣ X 1 ∣ = x U 1 ( x 2 ) = 2 x 2 = x
| X_{1} | = x
\\ U_{1} \left( {{x} \over {2}} \right) = 2 {{x} \over {2}} = x
∣ X 1 ∣ = x U 1 ( 2 x ) = 2 2 x = x
For n = 2 n=2 n = 2 ,
∣ X 2 ∣ = x 2 − 1 U 2 ( x 2 ) = 4 ( x 2 ) 2 − 1 = x 2 − 1
| X_{2} | = x^2 - 1
\\ U_{2} \left( {{x} \over {2}} \right) = 4 \left( {{x} \over {2}} \right)^2 - 1 = x^2 - 1
∣ X 2 ∣ = x 2 − 1 U 2 ( 2 x ) = 4 ( 2 x ) 2 − 1 = x 2 − 1
Assume the proposition P ( n ) P(n) P ( n ) holds for n = k − 1 n=k-1 n = k − 1 and n = k n=k n = k .
Recurrence relation of Chebyshev polynomials of the second kind :
U n + 1 ( x ) = 2 x U n ( x ) − U n − 1 ( x )
U_{n+1} (x) = 2x U_{n} (x) - U_{n-1} (x)
U n + 1 ( x ) = 2 x U n ( x ) − U n − 1 ( x )
From Part 1,
∣ X k + 1 ∣ = x ∣ X k ∣ − ∣ X k − 1 ∣
| X_{k+1} | = x | X_{k} | - | X_{k-1} |
∣ X k + 1 ∣ = x ∣ X k ∣ − ∣ X k − 1 ∣
implying,
U k + 1 ( x 2 ) = x U k ( x 2 ) − U k − 1 ( x 2 )
U_{k+1} \left( {{x} \over {2}} \right) = x U_{k} \left( {{x} \over {2}} \right) - U_{k-1} \left( {{x} \over {2}} \right)
U k + 1 ( 2 x ) = x U k ( 2 x ) − U k − 1 ( 2 x )
Hence,
∣ X k + 1 ∣ − U k + 1 ( x 2 ) = x [ ∣ X k ∣ − U k ( x 2 ) ] − [ ∣ X k − 1 ∣ − U k − 1 ( x 2 ) ]
| X_{k+1} | - U_{k+1} \left( {{x} \over {2}} \right) = x \left[ | X_{k} | - U_{k} \left( {{x} \over {2}} \right) \right] - \left[ | X_{k-1} | - U_{k-1} \left( {{x} \over {2}} \right) \right]
∣ X k + 1 ∣ − U k + 1 ( 2 x ) = x [ ∣ X k ∣ − U k ( 2 x ) ] − [ ∣ X k − 1 ∣ − U k − 1 ( 2 x ) ]
From the assumption, ∣ X k ∣ = U k ( x 2 ) \displaystyle | X_{k} | = U_{k} \left( {{x} \over {2}} \right) ∣ X k ∣ = U k ( 2 x ) and ∣ X k − 1 ∣ = U k − 1 ( x 2 ) \displaystyle | X_{k-1} | = U_{k-1} \left( {{x} \over {2}} \right) ∣ X k − 1 ∣ = U k − 1 ( 2 x ) imply
∣ X k + 1 ∣ − U k + 1 ( x 2 ) = 0
| X_{k+1} | - U_{k+1} \left( {{x} \over {2}} \right) = 0
∣ X k + 1 ∣ − U k + 1 ( 2 x ) = 0
By mathematical induction , P ( n ) P(n) P ( n ) is true for n ∈ N n \in \mathbb{N} n ∈ N .
■